PENGAWETAN DUA JENIS KAYU BENTUKAN DENGAN BAHAN PENGAWET BFCA SECARA RENDAMAN DINGIN (Cold Soaking Treatment of Two Wood Species of Moulding Products Using BFCA Preservative) - Sasa Abdurrohim; Bakir Ginoga (Jurnal Penelitian Hasil Hutan, 1993)
Moulding products made of two wood species in the form of coves were treated with BFCA preservative by cold soaking. The length of the test pieces were 30 cm. The duration of cold soaking treatment were 2, 4, 6 and 8 days, with preservative concentrations of 5 and 10 percent. The test results, after taking both retention and penetration requirements into consideration for wood uses under roof and in the open air without ground contact, showed that both wood species could be satisfactorily treated under experimental conditions. The treatment schedules proposed for both species are also presented in this paper. The average swelling of those species after treatment comparing to dimension are relatively small, therefore could be avaidable and has no affect on their use.